Mindfulness-Based Stress Reduction as a Stress Management Intervention for Cancer Care - Sarah E. Rush PhD, CHES; Manoj Sharma MBBS, MCHES, PhD, FAAHB (SAGE Publishing, 2017)
Cancer is acknowledged as a source of stress for many individuals, often leading to suffering, which can be long-lasting. Mindfulness-based stress reduction offers an effective way of reducing stress among cancer patients by combining mindfulness meditation and yoga in an 8-week training program. The purpose of this study was to inspect studies from October 2009 to November 2015 and examine whether mindfulness-based stress reduction can be utilized as a viable method for managing stress among cancer patients. A systematic search from Medline, CINAHL, and Alt HealthWatch databases was conducted for quantitative articles involving mindfulness-based stress reduction interventions targeting cancer patients. A total of 13 articles met the inclusion criteria. Of these 13 studies, 9 demonstrated positive changes in either psychological or physiological outcomes related to anxiety and/or stress, with 4 describing mixed results. Despite the limitations, mindfulness-based stress reduction appears to be promising for stress management among cancer patients.